High-throughput assessment of vacancy formation and surface energies of materials using classical force-fields. (7th September 2018) - Choudhary, Kamal; Biacchi, Adam J; Ghosh, Supriyo; Hale, Lucas; Walker, Angela R Hight; Tavazza, Francesca
Abstract: In this work, we present an open access database for surface and vacancy-formation energies using classical force-fields (FFs). These quantities are essential in understanding diffusion behavior, nanoparticle formation and catalytic activities. FFs are often designed for a specific application, hence, this database allows the user to understand whether a FF is suitable for investigating particular defect and surface-related material properties. The FF results are compared to density functional theory and experimental data whenever applicable for validation. At present, we have 17 506 surface energies and 1000 vacancy formation energies calculation in our database and the database is still growing. All the data generated, and the computational tools used, are shared publicly at the following websites:www.ctcms.nist.gov/ knc6/periodic.html, https://jarvis.nist.gov andhttps://github.com/usnistgov/jarvis . Approximations used during the high-throughput calculations are clearly mentioned. Using some of the example cases, we show how our data can be used to directly compare different FFs for a material and to interpret experimental findings such as using Wulff construction for predicting equilibrium shape of nanoparticles. Similarly, the vacancy formation energies data can be useful in understanding diffusion related properties.